The Physiotherapy Study Program PENATALAKSANAAN FISIOTERAPI PADA KASUS LOW BACK PAIN (LBP) e.c ISCHIALGIA DENGAN TERAPI SHORT WAVE DIATHERMY (SWD) DAN WILLIAM FLEXION EXERCISE DI RS. BHAYANGKARA PUSDIK BRIMOB WATUKOSEK - Khoiroh, Muhimmatul; Rohmah, Eliya; Hidayah, Agus Nurul (Jurnal Delima Harapan, 2024)
Background : Currently, lifestyles are increasingly deviating from healthy lifestyle standards, and as a result many people are suffering from diseases with neurological symptoms such as musculoskeletal problems, one of which is LBP or Low Back Pain which is lower back pain that occurs in the paralumbar area. There are several etiologies of LBP, one of which is Ischialgia or Sciatic Pain. Ischialgia is a feeling of pain and tingling from the lower back to the knee due to pinching of the sciatic nerve. Lower back pain can be reduced in intensity using Short Wave Diathermy (SWD) and William Flexion Exercise. Results of preliminary studies at the hospital's medical rehabilitation clinic. Bhayangkara Pusdik Brimob Watukosek in 2023 found a total of 87 cases of LBP e.c. Ischialgia patients, therefore the author was interested in finding out the effectiveness of these two modalities for one of the respondents to be used as a research subject for scientific writing using the case study method. Objective: Have experience regarding the physiotherapy management of LBP e.c. Ischialgia with Short Wave Diathermy therapy and William Flexion Exercise at the hospital. Bhayangkara Pusdik Brimob Watukosek. Method: In the case of Low Back Pain e.c Ischialgia, Short Wave Diathermy therapy and William Flexion Exercise were used. Results: Physiotherapy treatment during 6 therapy sessions showed a decrease in pain, an increase in joint range of motion, an increase in muscle strength values, and an increase in functional activity. Conclusion: Using the two modalities of SWD and William Flexion Exercise for 6 therapy sessions, it was found that there was a reduction in pain, an increase in joint range of motion, an increase in muscle strength values, and an increase in functional activity.